A low-power dynamic comparator for low-offset applications - Khorami, Ata; Saeidi, Roghayeh; Sachdev, Manoj; Sharifkhani, Mohammad (Elsevier, 2019)
In this paper, a low-power method for double-tail comparators is introduced. Using the proposed method, the power consumption of the pre-amplifier which is the dominant part is reduced considerably. Thanks to this method, the pre-amplifier is not able to draw more than required amount of power, therefore, the power is saved. Post layout and corner simulation results show the power consumption is reduced by about 40%. Moreover, several Monte-Carlo (M) simulations suggest the proposed method results in about 20% offset reduction at the cost of 5% area and 10% speed degradation.
The final publication is available at Elsevier via https://doi.org/10.1016/j.vlsi.2019.07.001. © 2019. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/by-nc-nd/4.0/
Keywords: dynamic comparators; low-power; pre-amplifier